Виробництво суріміподібного матеріалу з механічно обваленого м’яса індика - Галенко, Олег Олександрович; Кравчук, Валентина Вадимівна; Медяник, Марія Олександрівна (My University, 2021)
Сучасний рівень соціально-економічного стану нашої країни, дефіцит вітчизняної м’ясної сировини (значною мірою – яловичини та свинини), а також скороспілість, інтенсивний ріст, висока відтворна здатність, продуктивність і життєздатність сільськогосподарської птиці зумовлюють необхідність розробки і застосування прогресивних науково обґрунтованих технологій її переробки. The impacts of washing solutions on mechanically deboned turkey meat (MDM) was evaluated with the aim to produce surimi-like material using solutions of succinic and lactic acid. Study of chemical composition of washed samples found that moisture content at the end of the study was 87.6% –92.7%, fat 1.04% –3.2%, protein 17.4–18.2%, ash 0.079–0.086%. The number of washing significantly influenced the increase in moisture content and the reduction of fat content. Obtained surimi-like material may have a moisture content in the range of 73 to 80%, but 78% moisture content is technologically the best.
Keywords: кафедра технології м’яса і м’ясних продуктів; індики; сурімі; м’ясопродукт; механічне обвалювання; turkeys; surimi; meat product; mechanical rolling